"A Mix Methodology Study Evaluating Perceptions Among Pharmacy Stakeholders In Two States Of Libya Towards The Need For Social Pharmacy Courses In Pharmacy Curriculum" - Abrika, Omar Saad Saleh (2013)
The pharmacy profession in many parts of the world had changed over the years due to the evolution of pharmacy practice from product to patient oriented services. Within this context, there is a need for the modern pharmacy practitioner to be well-equipped with appropriate social and human skills in order to better serve the population. In response to this need, in majority of developed nations, social pharmacy subjects have been formally integrated in the pharmacy curriculum in order to prepare a holistic future practitioner who will be able to understand and respond towards the socio-behavioural aspects of health and medication use among patients. Although the incorporation of social pharmacy topics into the pharmacy curriculum of developed countries has been promoted during the last two decades, the inclusion of these subjects as standard topics in many developing countries is poorly documented and similar case prevails in Libya. Understanding social pharmacy components can really help to fulfil the important mission for the provision of pharmaceutical care. It is therefore imperative to ascertain the knowledge and perceptions of pharmacy academics, practitioners and final year pharmacy students about the concepts of social pharmacy in the current Libyan pharmacy curriculum.